Localized electronic vacancy level and its effect on the properties of doped manganites - Juan, Dilson (2021)
Oxygen vacancies are common to most metal oxides and usually play a crucial role in determining the properties of the host material. In this work, we perform ab initio calculations to study the influence of vacancies in doped manganites La(1−x)SrxMnO3, varying both the vacancy concentration and the chemical composition within the ferromagnetic-metallic range (0.2<x<0.5). We find that oxygen vacancies give rise to a localized electronic level and analyse the effects that the possible occupation of this defect state can have on the physical properties of the host. In particular, we observe a substantial reduction of the exchange energy that favors spin-flipped configurations (local antiferromagnetism), which correlate with the weakening of the double-exchange interaction, the deterioration of the metallicity, and the degradation of ferromagnetism in reduced samples. In agreement with previous studies, vacancies give rise to a lattice expansion when the defect level is unoccupied. However, our calculations suggest that under low Sr concentrations the defect level can be populated, which conversely results in a local reduction of the lattice parameter. Although the exact energy position of this defect level is sensitive to the details of the electronic interactions, we argue that it is not far from the Fermi energy for optimally doped manganites (x∼1/3), and thus its occupation could be tuned by controlling the number of available electrons, either with chemical doping or gating. Our results could have important implications for engineering the electronic properties of thin films in oxide compounds.